Forensic Monitoring Project Report: Ozren Mountain Region, Including Stog, Gostovici, Zavidovići, etc - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Hudson, Page From 10-27 November 1997 officials from a variety of governmental and international organizations searched the Ozren Mountain region for mass graves, particularly for a grave of about 58. Overall 23 bodies were recovered. It is believed that 58 Serb prisoners were executed in the region in July of 1995 though officials from the RS 16th Brigade contended that 20 of the 21 recovered bodies were their troops lost in fighting in the region in the summer of 1995. Place of Exhumation: Ozren region Exhumation Site: Stog, Zavidovići, Ribnica Date of Exhumation: 10-27 November 1997 Minimum Number of Exhumed Individuals: 023